Knight eaudiobook - Zahn, Timothy (Chronicle of the Sibyl's War, 2019)
Nicole Hammond was just trying to survive on the streets of Philadelphia. Then she and her partner Bungie were abducted by a race of mysterious moth-like aliens and taken to a strange ship called the Fyrantha . Now she is a Sibyl, a special human that has the ability to communicate with the aliens and their ship, and no one is happy. Competing factions control different parts of the Fyrantha with the humans and other sentient aliens caught in the middle. But Nicole is done being bullied, and now she has a plan to take control of the ship. She just has to outsmart war profiteers and slavers to do it.